ENT530 : WAFA Sdn. Bhd / Nurlia Nurdin, Mumaiza Mohd Nasir and Nurhidayah Abdul Latif - Nurdin, Nurlia; Mohd Nasir, Mumaiza; Abdul Latif, Nurhidayah (2017)
By referring to our product motto, the concept is towards helping others who are in needs; our company had decided to produce an application which is able to help people in terms of financial aids, health, society volunteerism, and clothes. We provide an online medium by preparing sources of place for giving and asking assistance. It is our motto that technology will always strive for a better future. With our new application which can be downloaded through Android playstore, Apple store, people can voice out their daily difficulties and also can help others who are in needs. This product is called "Wly Donation". My Donation is a new charity application which aimed to help people in everyday life